Characterization of Nonmetallic Inclusions in Low‐Alloyed Steels Using Pulse Distribution Analysis Optical Emission Spectroscopy and Offline Investigation Methods. Issue 11 (27th July 2021) - Du, Hongying; Yang, Annika; Karasev, Andrey V.; Jönsson, Pär G.
Abstract : The characteristics of nonmetallic inclusions (NMIs) in low‐alloyed steel samples taken during ladle treatment before and after Ca treatment are evaluated using the pulse distribution analysis optical emission spectroscopy (PDA/OES) method, INCA‐Feature investigations of inclusions on a polished surface of steel samples, and 3D investigations of NMIs after electrolytic extraction (EE) of steel samples. The investigation results of NMIs using the different methods were compared. The PDA/OES results show a clear tendency of a change in the average composition and quantity of NMIs during ladle treatment, which correlates well with the results obtained from the other two methods. Overall, it is found that the application of the PDA/OES method is appropriate to enable a fast online evaluation of inclusion compositions and their behaviors during steelmaking. This, in turn, provides the means for establishing an online control and correction of technological operations of the ladle treatment to implement necessary modification of NMIs to improve the cleanliness of steels and avoid clogging problems during casting. Abstract : Herein, the characteristics of nonmetallic inclusions (NMIs) in low‐alloyed steel samples before and after Ca treatment are evaluated using the pulse distribution analysis optical emission spectroscopy (PDA/OES), INCA‐Feature, and electrolytic extraction (EE) methods. The results are compared. Overall, the PDA/OES method enables a fast online evaluation of inclusion compositions during steelmaking, which can be applied to avoid possible clogging problems.